Diastasis recti in the Beninese population: Cross-sectional study from normal values to diagnosis - Yollande S. Djivoh; Toussaint Kpadonou; Thierry Puttemans; Dominique De Jaeger (AOSIS, 2022)
Background: Diastasis recti is diagnosed when the interrecti distance (IRD) is larger than a threshold value. Published thresholds were measured at rest with ultrasound while in Benin physiotherapists use calipers during abdominal contraction. Objectives: The aim was to define IRD threshold values measured with calipers in Beninese participants in order to diagnose diastasis recti in a clinical environment and identify women needing abdominal rehabilitation. Method: Interrecti distance was measured using ultrasound and calipers. Linea alba stiffness was assessed by palpation, abdominal strength and endurance by manual testing. In men and nulliparous women, IRD threshold values were defined as IRD P90. In postpartum women, IRD P80 and a threshold defined with a receiver operating characteristics (ROC) curve based on linea alba stiffness were used. In these women, abdominal strength and endurance were compared depending on IRD threshold and linea alba stiffness with a Mann Whitney test. Results: In 391 Beninese participants, the IRD threshold measured with calipers was 17 mm in men, 15 mm in nulliparous and 18 mm (15 mm with ROC curve) in postpartum women. Postpartum women with an IRD above 18 mm had significantly lower abdominal strength. Those with a slack linea alba had significantly lower abdominal strength and endurance. Conclusion: The defined IRD threshold values can be used in a Beninese clinical environment. Future studies should confirm whether they can be applied to other African populations. Clinical implications: Abdominal rehabilitation should be recommended to postpartum women whose IRD is above the threshold values but also in cases of slack linea alba and poor abdominal function.